CASALE MONFERRATO REMEDIATION: ASBESTOS POLLUTION AND SAFETY MEASURES TO PROTECT WORKERS AND ENVIRONMENT: Received: 23rd August 2023 Revised: 22nd December 2023, 26th December 2023, 16th January 2024, 19th January 2024 Accepted: 14th September 2023 - Federica Paglietti; Paolo De Simone; Sergio Malinconico; Sergio Bellagamba (MATTER: International Journal of Science and Technology, 2024)
Asbestos is considered one of the most harmful occupational carcinogens causing more than 100,000 deaths per year and exposure to airborne asbestos ﬁbers is held responsible for half of the deaths from occupational cancer (caused by mesothelioma, asbestos-related cancer and asbestosis). Because of this, this substance is now banned in 52 Countries, including Italy, which prohibited the extraction, and marketing of asbestos in 1992. Many areas have therefore been identified in this European Country as highly contaminated by asbestos. Among them also the area of Monferrato, which includes the Municipality of Casale Monferrato and 46 neighboring municipalities. The Eternit asbestos cement plant, located in the municipality of Casale, caused the contamination. The aim of this paper is to describe the complex remediation activities conducted in this wide area, located in northern Italy, highlighting the main phases and the most important issues during the remediation execution; moreover the purpose is to recall the appropriate prevention and protection measures to adopt to prevent new asbestos exposures and to emphasize their importance. This study can serve as an important reference for the academic participants involved in this field at European or international level.